Validation Issues of a Space-based Methane Lidar - Kiemle, Christoph; Fix, Andreas; Ehret, Gerhard; Flamant, Pierre (2014)
Space-based lidar missions targeting greenhouse gases are expected to close observational gaps, e.g., over subarctic permafrost and tropical wetlands, where in-situ and passive remote sensing techniques have difficulties. In the frame of a joint climate monitoring initiative, a “Methane Remote Lidar Mission” (MERLIN) was proposed by the German and French space agencies DLR and CNES. MERLIN is now in Phase B, in which all mission components are planned in detail. Launch is foreseen in 2019. The instrument is an integrated path differential absorption (IPDA) lidar which, installed on a low earth orbit platform provided by CNES, uses the surface backscatter to measure the atmospheric methane column. The globally observed concentration gradients will primarily help inverse numerical models to better infer regional methane fluxes. The lidar signals are able to travel through optically thin cloud and aerosol layers without producing a bias, and MERLIN’s small field of view, of order 100 m, is expected to provide observations in broken cloud environments, often encountered in the tropics. As IPDA is a novel technique, calibration and validation will be essential. It is foreseen to validate MERLIN by under-flying the satellite with another IPDA lidar, CHARM-F, and a passive remote sensor, both airborne. However, active and passive remote sensors have different, pressure and temperature dependent measurements sensitivities (weighting functions), different fields of view, and do not sample the total methane column on-board an aircraft. Furthermore, since the methane profile is not constant, its column depends on the height of the boundary layer and of the tropopause. We investigate the impact of these issues on the expected validation accuracy, and we examine whether the ground-based Total Carbon Column Observing Network (TCCON) may be useful for validation, too. Finally, validation opportunities are dependent on the location and size of cloud-free regions, since clouds with optical thickness > 1 hinder MERLIN ...